CLINICAL AND IMMUNOBIOCHEMICAL MARKERS IN THE DIAGNOSIS OF BRONCHIAL ASTHMA COMBINED WITH TYPE 2 DIABETES MELLITUS - Faizullaeva N. Ya.; Mukhtorov Sh. M.; Raufov A. A.; Nabieva U. P.; Yarmukhammedov A. S. (Web of Journals Publishing, 2025)
The aim of the study was to investigate clinical, laboratory and immunobiochemical markers in patients with bronchial asthma (BA) combined with type 2 diabetes mellitus (T2DM). A comparative analysis of clinical manifestations, carbohydrate metabolism parameters, fibrinolysis and the antioxidant system was performed.
Keywords: Bronchial asthma, type 2 diabetes mellitus, immunobiochemical markers, superoxide dismutase, tPA, PAI-1, diagnostics.